Central America : regional integration and economic development - Hansen, Roger D. (National Planning Association WashingtonUS, 1967)
Evaluates the Central American efforts to implement and sustain development progress. Discusses several basic development problems facing the Central American republics. Assesses the difficulties facing the Central American integration effort and the magnitude of the successes already achieved. Suggests the generalizations from the Central American experience which may be of significance to development progress in other areas of the world.